Answer:
x=65/14
Step-by-step explanation:
(x-10)/(x-4)=50/-6
-50/6=-25/3
(x-10)/(x-4)=-25/3
x-10=-25/3(x-4)
x-10=-25/3x+100/3
x-(-25/3x)=100/3+10
x+25/3x=130/3
28/3x=130/3
x=(130/3)/(28/3)
x=(130/3)(3/28)
x=130/28
x=65/14
Answer:
i dont know sorry
Step-by-step explanation: cant explain it
<h3>(-3j²k³)²(2j²k)³</h3>
(-3j²k³)²(2j²k)³ = <em>When a power is raised to a power the exponents have to be multiplied.</em>
= (-3²j⁽²*²⁾k⁽³*²⁾)(2³j⁽²*³⁾k³) = <em>We can take out the constants</em>
= (9)(8)(j⁴k⁶)(j⁶k³) = <em>We can group the same variables</em>
= 72(j⁴j⁶)(k⁶k³) = <em>When multiplying two powers that have the same base, you have to add the exponents.</em>
= 72 j⁽⁴⁺⁶⁾k⁽⁶⁺³⁾ = 72j¹⁰k⁹
Answer = 72j¹⁰k⁹
Hope this helps!
I think it’s the third option
The equation x^2 - 6x + 9 is a perfect square and when factored out it becomes C. ) It is a perfect square (x - 3)^2